Microbial-driven valorization of tannery sludge for fatty acids production: unraveling microbiome activity and functional redundancy - Tonanzi, Barbara; Massimi, Alessio; Valentino, Francesco; Tuci, Giulia Adele; Gottardo, Marco; Rossetti, Simona; Crognale, Simona (Frontiers in Microbiology, 2025)
The tannery sludge, with its high content of organic and inorganic compounds often hazardous to the environment, represents a major challenge in industrial waste management. Among the strategies to mitigate its impact, the biological production of fatty acids can be considered a cost-effective and sustainable solution. For the first time, this study investigated in depth the microbial community's composition and dynamics during anaerobic fermentation of tannery sludge to produce short-chain fatty acids (SCFAs). Systems with varying hydraulic retention times (HRT) and temperatures were explored, utilizing oxidative (Ox) and thermal (Th) pretreatments to enhance organic matter bioavailability. Mesophilic Ox reactors (Ox_4, Ox_8) achieved stable SCFAs production, primarily acetic acid. Ox_8, with longer HRT than Ox_4, showed higher organic matter conversion (0.32 ± 0.01 and 0.25 ± 0.01 g CODSCFA/g VS, respectively) and bacterial metabolic activity (FISH/CARD-FISH ratio of 0.8 and 0.9, respectively) as highlighted by microbiological analysis. Thermophilic Th reactors (Th_4, Th_8) yielded highest SCFAs production especially at longer HRTs (0.4 ± 0.01 g CODSCFA/g VS). The cutting-edge biomolecular approach herein applied has elucidated microbial community diversity and metabolic functionalities. Ox systems were dominated by Actinobacteria, Bacteroidetes, and Firmicutes, with Proteiniphilum as the key SCFAs producer. In contrast, Th reactors were mainly colonized by Coprothermobacteraeota and Firmicutes, with Coprothermobacter sp. playing a central role in SCFAs synthesis. Despite the compositional differences, both systems exhibited a noteworthy proteolytic functional redundancy, primarily linked to the substrate used. Among the first explorations, this research provides critical insights into the microbial adaptability and resilience of these biological systems.